OPTIMASI UDARA PANAS KELUARAN KOLEKTOR ENERGI SURYA - Yazmendra Rosa; Hanif Hanif; Zulhendri Zulhendri (Jurnal Teknik Mesin, 2004)
Indonesia is one of the countries which has high intensity solar radiation. This is very useful in term to exploite solar radiation for drying processes. However, most drying processes are done naturally. This method has many constraints. By improvement of solar collector technology, the drying processes could be done more better. Unfortunately, most solar collectors still have many limitation due to generating high output temperature. Therefore, in this present study, the solar collector is tried to optimizing by enlarging area of frontal surface of solar radiation and increasing rate of air flow out in term to maximize the drying processes. Result shows that by flowing the air constantly (0, 122 m3/s) on 1 m2 surface area will generate output temperatur to approximately 90,2 oC